Pengalaman Siswa Sekolah Dasar dalam Mengelola Rasa Cemas Saat Presentasi di Depan Kelas Materi Struktur Lapisan Bumi pada Mata Pelajaran IPAS SDN Dukuh Kupang V Surabaya - Noviana Desiningrum; Amelia, Hikmah Putri; Gandes Larasati; Rivalda, Rizki Nabila Rivalda; Putri, Syafana Azelita Putri (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe elementary school students’ experiences in managing anxiety during classroom presentations on the topic of Earth’s layer structure in IPAS learning at SDN Dukuh Kupang V Surabaya. This research employed a qualitative descriptive approach involving 27 fifth-grade students selected through purposive sampling. Data were collected through in-depth interviews, presentation observations, and learning documentation. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing. The results indicate that most students experienced anxiety in physical, emotional, and behavioral forms, such as nervousness, trembling, and difficulty speaking. Anxiety was influenced by low self-confidence, limited mastery of the material, and classroom social pressure. However, students applied simple strategies to manage anxiety, including practicing, regulating breathing, and receiving peer support. Teachers also played an important role in creating a safe and supportive learning environment. These findings emphasize the importance of addressing students’ emotional aspects in IPAS learning.